Деякі властивості спечених твердосплавних виробів у вигляді кілець із різною величиною обмеження процесу усадки - Бондаренко, В.П.; Юрчук, М.О.; Сотникова, Л.Л. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The possibility to prepare high-quality cemented carbide products by the method which assures 100 % degree of limitation on shrinkage in sintering is shown. The alloys so prepared are more fine-grained. Possibilities of widening the ranges of using available molds in the cemented carbide production are opened up.